The Effect of Class Attendance on Academic Performance: The Role of Active Classroom Participation - Dilafruz Kuchkorova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Student absenteeism has become an increasingly common issue at Westminster International University in Tashkent (WIUT). This study explores the relationship between class absenteeism and academic performance based on a sample of 108 students enrolled during the 2018–2019 academic year. The sample includes students of varying ages, academic levels, and courses.